The Adoption of Digital Technologies in Supply Chains in the Manufacturing Area - Lena Magdalena; Muhammad Hatta; Mar’atus Solikhah (Jurnal Indonesia Sosial Teknologi, 2024)
The Ongoing COVID pandemic has hampered economic activity; Food is a basic need that must be fulfilled and cannot be postponed. During the current pandemic, business people need to pay attention to the situation and conditions, especially the limitation of economic activity in several regions. However, Digital technologies have been extensively studied in academic research and industry. Moreover, little is known about adopting digital technologies in manufacturing firms at a supply chain level. This paper aims to understand why and how manufacturing firms adopt digital technologies and the impact of the adoption on supply chains. This research includes the design of a Web-based Supply Chain Management application to facilitate inventory management, starting from the process of ordering goods from suppliers and procurement of goods to managing goods to customers. Digital technology in the supply chain in the manufacturing area helps companies to store goods management data, raw materials, inventories, deliveries, and daily deposits, and others that are still using manual systems or not yet computerized to maximize performance and also profits for the company, suppliers, including end customers. The study identifies that technological intelligence and supply chain cooperation are critical factors and proposes two-dimensional levels of adopting digital technologies according to their low-to-high degrees.